Development Of Boost Inverter Using Single Phase Matrix Converter Topology - F. Mohd Zin, M.; Baharom, R.; Mohd Yassin, I. (International Journal of Engineering and Technology, 2018)
This paper presents the development of boost inverter using a single phase matrix converter (SPMC). A new switching algorithm was developed to control the SPMC circuit topology to operate as a boost inverter. The pulse width modulation (PWM) technique was used to calculate the switching duty ratio to synthesize the output. As part of boost inverter operation, a safe-commutation switching algorithm has been applied to avoid the voltage and current spikes due to the effect of inductive loads. The simulation of the proposed converter was carried out in MATLAB/SIMULINK. Selected simulation are presented to verify the proposed operation.Â Â